Waste Analysis Using Lean Manufacturing in the Film Production Process Step 2 Ulama - Wahyu Sidiq Saputra; Muhammad Ridwan Andi Purnomo (Institut Teknologi Bisnis AAS Indonesia, 2021)
Abstract - The film Footsteps 2 Ulama produced by LSBO Muhammadiyah in collaboration with Ponpes Tebuireng Jombang is a semi-documentary film that tells the journey of Kyai Ahmad Dahlan and Kyai Hasyim Asy'ari. At the time of the production of the film Jejak step 2 Ulama in its implementation there were several problems such as delayed production schedules, human resources that were not as needed, scheduling errors, and also production defects in several scenes so that they had to be re-take or it could be said to be re-production to get maximum results, where these problems tend to result in waste or waste. Therefore, a study was conducted to analyze what kind of waste occurs and the most dominant using a lean approach. Based on the results of the study, it was found that waste waiting is the most dominant waste with a weight of 27.11%, then followed by waste over production and excess processing with the same weight of 20.33%, waste defect 13.55%, waste transportation 11.86%, motion 5.08% and inventory 1.69%. From the mapping using process activity mapping, a total of 32 types of activities were obtained, of which 12 were value added activities with a percentage of 50.36%, then 9 of them were necessary non-value added activities with a percentage of 13.13%, and 11 activities included in the non-value category. added with a percentage of 26.49%.